asdf - Aflah Dwi Oktoriando; Miftahul Fauziah (Proceedings Series on Physical & Formal Sciences, 2026)
Public transportation is essential in reducing congestion, pollution, and dependence on private vehicles. To support sustainable mobility, the Yogyakarta Regional Government has operated the Trans Jogja electric bus since 2023 on the Ngabean–Malioboro corridor, which serves as a strategic urban route. This study aims to evaluate operational performance and passenger satisfaction in order to provide recommendations for service improvement. The research method refers to the Directorate General of Land Transportation Decree No. SK.687/AJ.206/DRJD/2002, focusing on operational indicators such as load factor, travel speed, cycle time, and headway. Passenger satisfaction was measured using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA), based on both primary and secondary data analyzed quantitatively. The results show that operational performance still needs improvement. The load factor was relatively low, at 17% on Thursday and 32% on Sunday. In addition, the average headway reached 31.23 minutes, the cycle time was 0.70 hours, and the average travel speed was only 14.25 km/h. On the other hand, IPA results demonstrated that key service attributes—such as safety equipment, air conditioning, driver behavior, and zero emissions—were well implemented. The CSI score of 91.39% indicates high passenger satisfaction. In conclusion, despite operational shortcomings, the service quality of the Trans Jogja electric bus is perceived positively. Ensuring continuous improvements in efficiency while maintaining service quality is crucial for the long-term success and sustainability of electric bus operations in Yogyakarta.